Location via proxy:   [ UP ]  
[Report a bug]   [Manage cookies]                

Uv Physics Academy: 28-08-2023 HINTS & SOLUTIONS

Download as pdf or txt
Download as pdf or txt
You are on page 1of 9

UV PHYSICS ACADEMY

28-08-2023 HINTS & SOLUTIONS


i /4
e + e−i /4  
( ) ( ) 1
1/2 1/2
1. i + −i = ei /2 + e −i /2
= 2  = 2  cos = 2  = 2
 2  4 2
1 1 1+ i 1+ i 1+ i 1 1
2. z= ;z =  ;z = 2 2 ;z = ; ( x, y ) =  ,  = ( 0.5,0.5 )
1− i 1− i 1+ i 1 −i 2 2 2
1/2 3/2
S S
 r .ds =  ( .r ) dV = 3V = 3a ; S = 6a 2  a =    3 
3
3.
V 6 6

R

RR

 A.dr =  ( ) ( ) y2 R3
4.   A .ds ;   A = ˆj ( y − z ) + kˆ ( y − z ) ;   A .ds = ( y − z ) dxdy =
  x =
s S 0 0
2 0 2

( ) ( )
n n
5. m = n  z = rei is Analytic. m = −n  z = re−i is Not Analytic.

6. F = ( x − y + z ) iˆ + ( x + y + z ) ˆj + ( 2 x − 3 y + z ) kˆ ;  F .dr =    Fds ;
iˆ ˆj kˆ
  
 F = = iˆ ( −3 − 1) − ˆj ( 2 − 1) + kˆ (1 + 1) ;   F = −4iˆ − ˆj + 2kˆ ;
x y z
x− y+z x + y + z 2x − 3y + z
2 2

 F .dr = 
0
ˆ

ˆ = 2 dxdy = 2 r 2 = 8
2kdxdyz
0

2 2
ˆ + ˆjx; x = 1 cos , dx = −1 sin  d ; y = 1 sin  , dy = 1 cos  d ; F .dr = 1 2 1 
F = −iy   sin  d +  6 cos  d =
2
7.
3 3 2 2 0
6 0
3

d
8. will be discontinuous at points where the delta-function blows up. i.e., at x3 − 7 x + 6 = 0
dx
 x3 − x 2 + x 2 − x − 6 x + 6 = 0  x2 ( x − 1) + x(x − 1) − 6(x − 1) = 0  ( x − 1)(x 2 + x − 6) = 0
d
 ( x − 1)(x 2 − 2 x + 3x − 6) = 0  ( x − 1)(x − 2)( x + 3) = 0  x = 1, 2,(−3) ⸪ will be discontinuous at
dx
x = 1, 2 & (−3)
9. Given:  (r) = (x + iy)f(r) = (rsin  cos + irsin sin  )f(r) = rf (r )sin ei The operator L z can be expressed as

Lz = −i  Lz (r ) = −i rf (r )sin   iei = rf (r )sin  ei =  (r ) Therefore,  ( r ) is an eigenfunction of L z

with eigenvalue .
i  d   d
10. Let  ( x ) be the desired eigenfunction. ∴ Oˆ ( x ) = 0   x  −i  + 2  = 0  x dx = −2
  dx  
d


dx
= −2.  ln = −2ln x + ln c [c is a constant] = ln x −2 + ln c   ( x ) = 2
x
( )
c
x

11. Eigenvalues of the spin operator S do not depend on direction ( and  ) . They are always  .
2
0 1 0
 
12. Sˆ x operator is expressed as, Sˆ x =
 1 0 1  . Therefore, the expectation value of Sˆ x for the spin-state  is,
2 
0 1 0
 0 1 0  2   1
  
( 2 1 −1) 1 =
1
Sˆ x =  Sˆ x  =  ( 2 1 −1)  1 0 1  1  = ( 2 + 1 − 1) =
6 2  0 1 0  −1 6 2  1 6 2 3 2
    
1 1  1 3 9
1 1 2 = 1 + 2 =
2
13. Pamp =  f  i = ; Probability = Pamp =
10   10 10 10
14.  Lˆx ,  Lˆx , Lˆ y   ;  Lˆx , Lˆ y  = i Lˆz ;  Lˆx ,  Lˆx , Lˆ y   = i  Lˆx , Lˆz  ;  Lˆx ,  Lˆx , Lˆ y   = 2
Lˆ y
            
15. A = ( a + b )1 + ( a − b ) 2 ;  of A = 1 ( a + b ) + ( a − b ) ;  of A = 1 2 a 2 + b 2
2 2
( )
21. The real part & imaginary part of a complex analytic function, satisfy the Cauchy Riemann equations
u v u v
= & =− Here, f (z) = (− x 2 + xy + y 2 ) + i(ax2 + bxy + cy 2 ) = u( x, y) + iv(x, y)
x y x x
u v
According to 1st equation, = = −2 x + y = bx + 2cy Comparing the co-efficient of x & y on both sides, we
x y
1 u v
have b = −2, c = According to 2nd Equation = − = x + 2 y = −(2a x + by )
2 y x
1
Comparing co-efficient of x on both sides, we have 1 = −2a  a = −
2
M
( ) (
I = e y + cos x sin y dx + e + sin x cos y dy , Let M = e y + cos x sin y  ) = e x + cos x cos y and
x x x
22.
C
y
N M N M N
N = e x + sin x cos y  = e x + cos x cos y Since =  I = 0 Note: If = , then vector function is
x y x y x
conservative and hence line integral (work done) along a closed path is zero
1/3
 i   + 2 n   i 2in i 1 2 1 4
i  +  i  +  i 5i 3i
23. 3
i = e  2 
; ( n = 0,1,.....) = e 6 .e 3 ; ( n = 0,1,2,....) = e 6 , e  6 3  , e  6 3  = e 6 , e 6 , e 2 ; Therefore, the
 
i 5i
  5 5   1
roots are, z1 = e 6 = cos
6 6
+ i sin =
1
2
( )
3 + i ; z2 = e 6 = cos
6
+ i sin
6
( )
= − cos + i sin = i − 3 and
6 6 2
3i
3 3
z3 = e 2 = cos + i sin = −i
2 2
The given circle is, x2 + y 2 + 2x = 0  ( x + 1) + y 2 = 1 ; This is a circle of unit radius centered at (-1, 0). Now,
2
24.
i j k
  
F = yiˆ − xjˆ    F = = kˆ ( −1 − 1) = −2kˆ ; From Stokes’s theorem for an open surface S enclosed by
x y z
y −x 0

 F .dr =  (   F ).dS = −2 kˆ.( dSkˆ ) = −2   1 [Since, area of circle = S =  1 ]


2 2
a circle C, we have,
C S
= −2 = −6.29
1 1 1 1 1
25. Let z = rei . From the figure it is clear that, Z  1  r  1 Now, = i = e− i  =  1
z re r z r
1
Therefore, would be outside the unit circle.
z
26.  A.dz =  ydx − xdy  ; Putting x = 5cos and y = 5sin  ; dx = −5sin  d ; dy = 5cos d

C C
2 2 2
= 0
 (
sin  ( − sin  ) − cos  ( cos  d )  = − 25 sin 2  + cos 2  d = −25 d = −25  2 = −157.1
0
) 
0

   
27. ( )
 =  iˆ + ˆj + kˆ  x 2 y + yz = 2xyiˆ + x + z ˆj + ykˆ ; Therefore, 
2
( )
(1,2,−1)
= 4iˆ + 2kˆ ; Therefore, rat of
 x y z 
 iˆ + 2 ˆj + 3kˆ  4 + 6 10
change with distance in the direction of a = iˆ + 2 ˆj + 3kˆ , is  . ( aˆ ) = 4iˆ + 2kˆ.  ( )  = =
 14  14 14
iˆ ˆj kˆ
  
28. 
F = yiˆ − xjˆ; F .dl = 
s
curl Fds ; curl F =
x y z
; curl F = iˆ ( 0 ) + ˆj ( 0 ) + kˆ ( −1 − 1) ;

y −x 0
1 
curl F = −2kˆ;  curl Fds = −2 kˆ.kds
s

ˆ = −2 ds = −2 (Area of OPQ ) ; = −2  1 2 = −2

2

eˆx eˆ y eˆz
 
− yeˆx + xeˆy    2 x2 2 y2
;   E = eˆz  2 ;
1 1
29. E= ;  E = − + 2 −
 x + y 2 2 
x2 + y 2 x y z
( ) x + y2 ( )
2
x2 + y 2 x2 + y 2 
 
−y x
0
x + y2
2
x + y2
2

  2 
 2  x + y2    2 2 
  E = ez  2
ˆ −2 2 
;   E = eˆz  2 − 2 ;  E = 0 ;

x +y ( )x +y x + y2 
2 2
 x +y
2 2

  

 (   E ) ds = 0 ; This is not correct at (0, 0, 0). The function is not well defined.
s

− ydx + xdy
 (  E )da =  E.dl = 
s
x2 + y 2
; Let x = a cos  dx = −a sin  d , y = a sin   dy = a cos d ;

2
a 2 sin 2  d + a 2 cos 2  d
( )  d =  
2

s
  E da =  a2
=
0
0
= 2

r ( t ) iˆ + ˆj + kˆ
30. r ( t ) = tiˆ + t 2 ˆj + t 3 kˆ; t = 1; r ( t ) = iˆ + ˆj + kˆ ; r ( t ) = 1 + 1 + 1 = 3; nˆ = = ;
r (t ) 3
This is parallel to the curve tangent to the curve is given by
dr
dr ˆ dr dr iˆ + 2 ˆj + 3kˆ
= i + 2tjˆ + 3t 2 kˆ; t = 1; = iˆ + 2 ˆj + 3kˆ ; = 9 + 4 + 1 = 14; nˆ = dt ; nˆ =
dt dt dt dr 14
dt
we can write  in the eigen basis of  .  = c1 1 + c2 2  c1 + c2 = 1
2 2
31.
 
1 2 1 2
Now,  Aˆ  = c12 a1 + c22 a2 = a1 + a2  c12 = , c22 = The average value of Â2 is
3 3 3 3
1 2
Aˆ 2 =  Aˆ 2  = c12 a12 + c22 a22 = a12 + a22 The uncertainty in  is
3 3
a12 2a22 a12 4a22 4a1a2
2 2a12 2a22 4a1a2 2
Aˆ = Aˆ 2 − Aˆ + = − − − = + − = a1 − a2
3 3 9 9 9 9 9 9 3
1  0
32. The eigenfunctions of the Hamiltonian are 1 =   with eigenvalue E1 = 2 H 0 & 2 =   with eigen
 0 1
Value E2 = 3H0 . Given:  t =0 =
1
( 1 + 2 ) The state at time t will be
2
 − 2iH0t 
1  −i 2  1 e  1   1
Et Et 2 iH 0 t 3iH 0 t
−i 1
 t =0\t = 
 1 e + 2 e  =  3iH 0t 
  (t )  (0) =  e e  
2  2 −  2   1
e 
1
2 iH 0 t
 iH 0 t
 iH 0 t

For these to be orthogonal,  (t )  (0) = 0 ; e  1 + e  = 0  e = −1 = ei (For Minimum time)


2  
H 0t 
 = t =
H0
33. The transmission co-efficient for a one-dimensional barrier is, for ( E  V0 ) .
1 2m
T= 2
, where,  = 2 ( E − V0 ) Let E = V0 , where,' ' is a constant.
V
1+ 0
sin 2 (  a)
4 E ( E − V0 )
2ma 2 2ma 2 2 2

Here,  a = 2 ( E − V0 ) = 2
 2
  −1 =  − 1 Now, here 800 particles are transmitted out of
8ma 2
800 8
900 particles. Therefore, the transmission co-efficient is T = =
900 9

8 1 1
sin 2  −2 1
 = =  2 =   = 2  E = 2V0
9 1+ 1 V0 2
2  4 ( − 1) 8
1+ sin   −1
8 4V02 ( − 1) 2 
34.  S x(1) S y(2) , S y(1) , S y(2)  =  S x(1) S y(2) , S y(1)  S y(2) + S y(1)  S x(1) S y(2) , S y(2)  (  S (1)
x S y(2)  = 0 )
=  S x(1) S y(1)  S y(2) S y(2) + S x(1)  S y(2) , S y(1)  S y(2) (  S (2)
y )
, S y(1)  = 0 =  S x(1) S y(1)  S y(2) S y(2) = i + S z(1) S y(2) S y(2)
2 2
i 3  1 0   1 0
Now, S y(2) S y(2) =  y(2) y(2) =  y(2) y(2) = I  i S z(1) S y(2) S y(2) =
I   
4 4 4  0 −1  0 1 
 1 0 1 0  1 0 0 0 
 1   0 
i  0 1 0 1  i 3 0 1 0 0 
=  =  
4 1 0 1 0   4  0 0 −1 0 
0  −1     
 1    0 0 0 −1
 0 1 0
 a3 d  a3 dx
35. We have operator, Dˆ = exp  2  . Let consider g ( x ) = ; Consider, y ( x ) =  g ( x) ∴
 3x dx  3x 2
dx d d d 
dy ( x ) =  = g ( x ) ; Now, my operator will be Dˆ = exp   ∴
g ( x) dy dx  dy 
d  dx dx
Dˆ  x ( y ) = exp    x / y  =   x ( y + 1) ; Now, y ( x ) =  y ( x) =  
 dy  g ( x) a3
3x 2
3x 2 x3
 x ( y ) = ay1/3 ∴  x ( y + 1)  =   x3 + a 3  ( )
1/3
= 
a 3
dx =
a 3  
h  P E − V0 V 1 1
36. Broglie wavelength (  ) = ; 1 = 2 = = 1− 0 = = = 0.33
P 2 P1 E E 9 3
i 2 / 5   0 / 2 ˆ  0 1 i 2 
37. X =
 3/5 
 ; SX = 
 / 2 0


1
; S X = X † Sˆ X X = −i 2 3 
5 2  1 0
 

;
 ( )
   3 
 3
Sˆ X =
10
(
−i 2 3  )
 = ( 0) = 0
 i 2  10
 
38. Â ( t ) ( t ) =  ( t + T ) …..(1); Operating Â−1 ( t ) in equation …..(2); Aˆ −1 ( t ) Aˆ ( t ) ( t ) = Aˆ −1 ( t ) ( t + T ) ;
 ( t ) = Aˆ −1 ( t ) ( t + T ) ; Clearly Â−1 ( t ) converts the state as it was ‘T’ time before Hence, Â−1 ( t ) ( t ) =  ( t − T )
2  
 r  − r /2 a0
1
 ( r , ,  ) = Y1,0 ( , ) ; ( r ) = r 2 − r   r  ( r , , )
2 2 2
39.  e ; r = r 2 sin  drd d
6a0  0 
3 2a
0 0 0
 2 
1
= 
r 5 e − r / a0 dr   Y ( , )Y ( , ) sin  d d ; spherical harmonic are orthonormal functions, so
*
5 1,0 1,0
24a0 0 0 0

r =
1
5
24a0 0 
r 5 e − r / a0 dr =
1
5
24a0
( 2 2
)
5!a06 = 5a0 ; Similarly, r = 30a0  ( r ) = 30a02 − 25a02 = 5a02 ; ( r ) = 5a0
2
40. (
Given:  xˆ 2 + pˆ 2 , e xˆ + e pˆ
 )( ) =  xˆ , e 2
 +  pˆ 2 , e xˆ  = xˆ  xˆ , e pˆ  +  xˆ , e pˆ  xˆ + pˆ  pˆ , e xˆ  +  pˆ , e xˆ  pˆ ; Now, we know
 

        
df  df 
that,  xˆ , f ( pˆ )  = i  pˆ , f ( xˆ )  =  −i  ; Therefore,  xˆ, e  = i e and pˆ  pˆ , e  = −i e ; Therefore,
pˆ pˆ xˆ xˆ
and
dpˆ  dxˆ 
Oˆ = i ( xeˆ pˆ
)
+ e pˆ xˆ − i ( pe
ˆ x
+ ex p = i ) (xˆ, e  −  pˆ , e )
pˆ x

 ˆ  ˆ  ˆ
46. Here,  ( x, y, z ) = xyz − 8 = 0 ; Therefore, the normal to the surface is given by  = i+ j+ k
x y k

= yziˆ + xzjˆ + xykˆ . Therefore, at the point P(1, 2, 4), the unit normal vector to the surface is nˆ P = P


P

( 2  4 ) iˆ + (1 4 ) ˆj + (1 2 ) kˆ 4iˆ + 2 ˆj + kˆ


=
8 +4 +2 2 2 2 21
=
2 21
1
(8iˆ + 4 ˆj + 2kˆ ) =
Therefore, option (b) is correct. Now, let

Q(x,y,z) be any point on the plane tangent to the surface  at point P(1, 2, 4) nˆ P will be perpendicular to the vector
 4iˆ + 2 ˆj + kˆ 
PQ = Q − P . ∴  
 . ( x − 1) iˆ + ( y − 2 ) ˆj + ( z − 4 ) kˆ = 0  4 x + 2 y + z + ( −4 − 4 − 4 ) = 0 
 21 
 4 x + 2 y + z = 12 ; Therefore, option (c) is correct.
47. The given surface S is a sphere of radius 3 units centered at origin. From divergence theorem,  F .dS =  ( .F ) dV ;
S V

 2  
Here, .F =
x y
( )
x + ( x ) + (1) = 2 x ; Therefore,  =
z  F .dS =  ( .F ) dV
S V
3  2


= 2 xdV = 2  (
( r sin  cos  ) r 2 sin  drd d ) (Since, x = r sin  cos  ) = 2 r 3dr sin 2  d
   cos  d =0.
V V 0 0 0

Therefore, option (b) is correct. Now, F (1,1, 2 ) = 1  iˆ + 1  ˆj + kˆ = iˆ + ˆj + kˆ ; We have, iˆ + ˆj + kˆ . −iˆ + ˆj = 0 ;


2
( )( )
iˆ ˆj kˆ
  
( )
Therefore, −iˆ + ˆj is perpendicular to F at (1, 1, 2). Therefore, option (c) is correct.   F =
x y z
=0;

x2 x 1
Therefore, from Stokes’s theorem,  F .dr =  (   F ) dS = 0 ; Therefore, option (d) is correct.
S S

dv du d u v
48. u −v = 0; ( u  v ) = 0 ; u  v = const ; so A = u  v = const ; nˆ = = const
dt dt dt u v
49.  F .dl =  (   F )
s
R−I
ds +  (   F )
s
R − II
ds ;  F .dl =  (   F )
s
R−I 
ˆ ˆ = 2 ds
ds = 2 kkds 
 r02
= 2 s = 2 =  r02
2
B
xdx y
50.  F.dl = 
A x2 + y 2
+
x2 + y 2
dy ;From given curve y = sin 

x = cos  dx = − sin  d ; y = sin   dy = cos d ; − cos  sin  d + sin  cos  d = 0 


iˆ ˆj kˆ
 2 x  2
   ˆ
51. F =  2 −  iˆ (a)   F = = i ( 0 ) − ˆj ( 0 ) + kˆ ( 0 ) = 0 ; F ( x ) is conservative.
x 2  x y z
2 x2
− 0 0
x2 2
(b) x = 0, F = 0, force passes through the origin, so angular momentum of particle about the origin is conserved.
(c) F = 0  x4 = 2  x =  2, but x > 0. So x = 2
Particle moves towards 2 . So the statemen “the particle moves towards the origin is false”.
2  3
52. A = 2 xiˆ +  yjˆ − 3 zkˆ ; A.ds =
s V
 
divAdV = 0 ; divA = 0  2 +  − 3 = 0;
6
+ −
6 6
=0;

  
+ − =0
3 6 2

iˆ ˆj kˆ
  
53. A=
1
r 2 ( )
− yiˆ + xjˆ ; r 2 = x 2 + y 2 ;  
A.dl = curlA.ds ; curl A =
x y z
;
s
−y x
0
x + y2
2
x + y2
2

ˆ
curl A = k  (
 x 2 + y 2 .1 − x ( 2 x )
+
)
x2 + y 2 − y ( 2 y )  (  2 2
) 2 2
 ; curl A = kˆ  y − x + x − y  = 0 . So
   
) ( ( ) ( )
2 2 2
 x2 + y 2 x2 + y 2   x2 + y 2 

 A.dl =  curl A.ds = 0  A.dl


s
is independent of ( x0 , y0 ) and its value is zero.

iˆ ˆj kˆ
  
54. F = yiˆ + xz 3 ˆj − zykˆ; F .dr =   curl F .ds ; curl F =
x y z
( ) ( )
; curl F = iˆ − z − 3xz 2 − ˆj ( 0 ) + kˆ z 3 − 1
c s

y xz 3 − zy

 curl F =  ( z )
− 1 ds ; z = 2; ds =  R2 = 4 ; = 7  ds = 7 s = 7  4 = 28
3

s s s

x+ y x− y
55. x1 =
2
; y1 =
2
; dx1dy1 = jdxdy ; where J is Jacobian of x1 , y1 w.r.t (x,y) ( )
x1 x1 1 1
x y
(
J x1 , y1 = ) y 1
y 1
;J =
1
2 2
−1
1 1
; J = − −  J = −1
2 2
x y 2 2
  
 cos 2 
56. The eigen vector of spin along nˆ = (ˆ, ˆ) with eigenvalue + is  + = 
2  ei sin  
 
 2
  
 cos 6  1  3 
  + ( = 600 , = 450 ) =    =    The initial state of electrons before entering the Stern-Gerlach
 i4   2  ei 4 
 e sin   
 6
 0
apparatus, will be i =   Therefore, the probability that electrons will have their spin parallel to the magnetic
1
2  2
  i
1 3 e4 1
filed in the Stern Gerlach apparatus is P = p = i  + ( , ) = (0 1) = =
2

2e 4 
i 2 4
 
Therefore, the percentage of particles with their spin parallel to the magnetic field in the Stern Gerlach
1
Apparatus will be, P  100% =  100% = 25%
4
57.
 ˆ 
Given Hamiltonian: Hˆ = 2 S 2 − 3Sˆz 2 − Sˆz
h (  x y )
 Sˆ 2 + Sˆ 2 = Sˆ 2 − Sˆ 2 
z

The eigenvalues of energy for this Hamiltonian for the s, m state is given by,
 ˆ 3 
Em = s, m Hˆ s, m = 2 s, m S 2 s, m − 2 s, m Sˆ 2z s, m − s, m Sˆzz s , m
ˆ
Now, S 2 s, m = 2
s ( s + 1) s, m & S z s, m = m s, m
 15 3   3
 Em = . 2 s ( s + 1) − − 3 m 2 −  m
.m 2 2
− .m =  s = 2 
 
2 2
4
3 3 1 1 3 15   
For s = , the possible values of m = − , − , , ;Now, Em = − 3   m2 + m
2 2 2 2 2 4  3 
3 15  9  3  15 27 3  
The ground state occurs for m =  Eground = E3 = − 3  + .  = − − = −3   + 
2 2 4  4 3 2  4 4 2  2
iHt

58. We know that, for a unit vector nˆ, ei ( .nˆ ) = I cos + i( .nˆ)sin  The state at time “t ” will be  (t ) = e  (0)


iH
t − 
i 0 B0
iˆ + ˆj    B0 
Here, e ( , nˆ )   nˆ =
=e  = I cos(t ) − i( , nˆ)sin( t)   = 
 2   
i sin( t )  1 0  i sin( t )  0 1   0 −i   
= i cos  t −  x +  y  = cos  t  −
2 
 + 
2  0 1   1 0   i 0 

 sin  t 
 cos  t −i (1 − i )  iHt
2 
=   (t ) = e  (0)
 −i (1 + i)sin( t ) 
 cos  t 
 2 
 (1 + i ) 
 cos  t − sin  t 
1 
 cos  t 
=  2  
  =  (1 − i )sin  t 
 (1 − i )sin  t  0  
 cos  t   2 
 2 
59. We know that, Lx = ypz − zp y ; Ly = zpx − xpz and Lz = xp y − ypx . Therefore,
(i)  px , Ly  =  px , ( zpx − xpz ) = −  px , x  pz = − ( −i ) pz = i pz ; Therefore, option (a) is correct.

(ii)  Lx , Py  = ( ypz − zp y ) , p y  =  y , p y  p z = i p z ; Therefore, option (b) is correct.

(iii)  x, Lz  =  x, ( xp y − yp x )  = −  x, p x  y = i p z ; Therefore, option (c) is incorrect.

(iv)  Lx , z  = ( yp z − zp y ) , z  = y  p z , z  = −i y ; Therefore, option (d) is correct.

i 2 1 2 i 2 2 2
60.  = 0 + 1 ,  = 0 −i 1 ; Â =   0 0 − 0 1+ 0 1 + i2 1 1;
3 3 5 5 15 15 15 15
 0 Aˆ 0 0 Aˆ 1   i / 15 −2 / 15  1 i −2 
matrix A =   ; A= ; A=  
 1 Aˆ 0 1 Aˆ 1   2 / 15 i 2 2 / 15  15  2 i 2 2 

− 2   ( x) 
2
61.  ( x ) = sech 2 ( x ) . + V ( x ) ( x ) = E ( x ) ; Now, = −2sech 2 ( x ) .tanh ( x ) = −2 tanh ( x ) ( x ) ;
2m x 2
x
 2
x 2
2 2
(
= −2 sech 2 ( x ) ( x ) + tanh ( x )  ( x )  = 2 − sech ( x ) + 2 tanh ( x )  ( x ) )
− 2 5 2
 −2sech 2 ( x ) + 4 tanh 2 ( x ) ( x ) + V ( x ) ( x ) = −  ( x)
2m   2m
−5 2 −5 2 3 2
( )
2
2 2 2 2 2
 V ( x) = − sech 2 ( x ) + tanh 2 ( x ) = − sech 2 ( x ) + =− 1 + 6sech 2 ( x )
2m m m 2m m m 2m
− 2
=
2m
( )
1 + 2sech 2 ( x )  a = 2, b = 6; aiˆ + bjˆ = a 2 + b 2 = 2 10
1 1
62. We know that, the eigen states of Sˆ x are,  x =   z +  z  …..(1);  x =
 
  z −  z  ; Therefore, we
2 2 

can write,  =
3
1

1
2
 x + x +i 6
2 1
3

i 
2

x − x
3
 1
 x + 
 6

i 
 = 
  x . Therefore,
3
1
+

 1 i  1 i  1 1 3 1
the probability of finding + / 2 upon measuring Sˆ x is, P1 =  +  −  = + = = ; Also,
 6 3  6 3 6 3 6 2

 =
1
3

1
2
 y + y +i 2  −i 

3  2 

y − y  =  1
6
+
1 
3
 1
 y + 
 6

1 
  y . Therefore, the
3
2
 1 1  1 1 2 1 2
probability of finding ( − / 2 ) upon measuring Sˆ y is, P2 =  −  =6+3− = − . The probability
 6 3 18 2 3
 2  2 2
of finding ( − / 2 ) upon measuring Sˆ z is, P3 =  i 
 −i  = . Also, if ( + / 2 ) is found upon measuring Sˆ z ,
 3  3  3
then the state collapses to  and a subsequent measurement of Sˆ will give a value ( − / 2 ) with probability 0.5.
z x

 − i 0   x1 
  
63. If X is the eigen vector corresponding to the eigen value  =  Then, ĤX =  X   −i − 0   x2  = 0 ; The
 0 −2  
 0  x3 
following equations are inferred from above.
(i) − x1 +  ix2 = 0  x1 = ix2 (ii) −i x1 −  x2 = 0  x1 = ix2 (iii) −2 x3 = 0  x3 = 0
2 2 2 2 2
According to normalization condition X † X = 1 ;  x1 + x2 + x3 = 1  −ix2 + x2 + 0 = 1
i / 2 
2 1 i  
 2 x2 = 1  x2 = ∴ x1 = ; Therefore, the required eigen vector is, X = 1 / 2  . Therefore, the
2 2  
 0 
 
2
1 − i 
2  i 1  1  
probability of finding he particle in the energy state  is given by X = − 0  1− i 
 2 2  5 
 1 
1 1 4
−i (1 − i ) + (1 − i ) =
2 2
= −i − 1 + 1 − i = = 0.4
10 10 10
1
64. The transmission co-efficient for a one-dimensional barrier is, for ( E  V0 ) . T = 2
, where,
V
1+ 0
sin 2 (  a)
4 E ( E − V0 )
2m
= 2 ( E − V0 ) Let E = V0 , where,' ' is a constant. Here,

2ma 2 2ma 2 2 2

a = 2 ( E − V0 ) = 2
 2
  −1 =  − 1 Now, here 800 particles are transmitted out of 900
8ma 2
800 8
particles. Therefore, the transmission co-efficient is T= =
900 9

8 1 1
sin 2  −2 1
 = =  2 =   = 2  E = 2V0
9 1+ 1 V0 2
2  4 ( − 1) 8
1+ sin   −1
8 4V02 ( − 1) 2 
 p2   p2 
65. The given commutator is [ A, B] =  + 2 x 2 , p 2 + x 2  =  , x 2  + 2[ x 2 , p 2 ]
 2   2 
1 3
= − [ x 2 , p 2 ] + 2[ x 2 , p 2 ]  [ x 2 , p 2 ] Now [ x2 , p2 ] = [x 2 , p] p + p[ x2 , p]
2 2
= x[ x, p] p + [ x, p]xp + px[ x, p] + p[ x, p]x = ixp + ixp + ipx + ipx ; [[ x, p] = i] = 2i ( xp + px)
3
[ A, B] = .2i( xp + px) = 3i(xp+ px)
2
ANSWER KEY (28.08.2023)
1.C 2.A 3.D 4.A 5.A 6.B 7.B 8.D 9.A 10.A 11.B 12.A 13.D 14.A 15.B
21.A 22.C 23.C 24.B 25.C 26.A 27.A 28.C 29.D 30.D 31.D 32.A 33.A 34.A 35.C
36.B 37.C 38.C 39.C 40.D 46.B 47.A 48.D 49.A 50.B 51.D 52.B 53.C 54.A 55.C
56.A 57.A 58.D 59.C 60.B 61.D 62.D 63.C 64.A 65.B

You might also like